2001
DOI: 10.1111/j.1553-2712.2001.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lower‐extremity Position on Cerebrospinal Fluid Pressures

Abstract: Abstract. Objective: To determine the effects of lower-extremity positioning on cerebrospinal fluid opening pressure (CSFp). The authors believed that during lumbar puncture (LP), CSFp does not meaningfully decrease when the lower extremities are extended from flexion, as is often suggested. Methods: In a convenience sample of adult patients who clinically required LP in an urban emergency department, three sequential CSFp measurements were obtained in either sequence A (knee, hip, and neck flexion [90Њ], then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…47,48 In the single identified study, CSF pressure changed little (Ͻ1.1 mm of water) with flexion of the lower extremities. 49 Various maneuvers, such as compressing the abdomen or the jugular vein (Queckenstedt's maneuver 50 ), can increase CSF pressure. 51 An obstruction to CSF flow prevents the normal rise and fall in pressure (positive Queckenstedt), but we were unable to find any studies describing the accuracy of this maneuver for detection of CSF outflow obstruction.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…47,48 In the single identified study, CSF pressure changed little (Ͻ1.1 mm of water) with flexion of the lower extremities. 49 Various maneuvers, such as compressing the abdomen or the jugular vein (Queckenstedt's maneuver 50 ), can increase CSF pressure. 51 An obstruction to CSF flow prevents the normal rise and fall in pressure (positive Queckenstedt), but we were unable to find any studies describing the accuracy of this maneuver for detection of CSF outflow obstruction.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…This may explain why only three patients in our study with pseudopapilledema had lumbar punctures performed. Although spinal fluid analysis is indicated to rule out other etiologies for raised intracranial pressure, opening pressure measurements can potentially vary in some patients based on many factors such as patient positioning with prone position recordings being higher than lateral decubitus, 21,22 Valsalva maneuvers, 23 effect of anesthesia, 24 and cannot be solely relied upon in making an accurate diagnosis. In our study, there was one patient who had CSF opening pressure measurement of 24 cm of H 2 O who had normal ultrasound and clinical features suspicious for papilledema and one patient in the pseudopapilledema category with 25 cm H 2 O of opening pressure.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated that the lower extremity position does not affect CSF pressure, others have shown a significant difference between OP in the flexed-and extended-leg positions. [3][4][5][6] In this survey, extended lower extremity position was not consistently maintained during OP measurement in the LD position. The clinical significance of this difference is debated, but lower extremity position could affect clinical decision-making in borderline cases.…”
Section: Discussionmentioning
confidence: 99%